Highly sensitive and selective colorimetric sensing of CO2 for biomedical applications - Shahina Shahid (21606167) (2022)
The concentration of carbon dioxide (CO2) in unhealthy people differs greatly from healthy people. High-precision CO2 detection with a quick response time is essential for many biomedical applications. A major focus of this research is on the detection of CO2, one of the most important health biomarkers. We investigated a low-cost, flexible, and reliable strategy by using dyes for colorimetric CO2 sensing in this study. The impacts of temperature, pH, reaction time, reusability, concentration, and dye selectivity were studied thoroughly. This study described real-time CO2 analysis. Using this multi-dye method, we got an average detection limit of 1.98 ppm for CO2, in the range of 50–120 ppm. A portable colorimetric instrument with a smartphone-assisted unit was constructed to determine the relative red/green/blue values for real-time and practical applications within 15 s of interaction and the readings are very similar to those of an optical fiber probe. Environmental and biological chemistry applications are likely to benefit greatly from this unique approach. Other Information Published in: 3 Biotech License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1007/s13205-022-03396-9